1991
DOI: 10.1111/j.1365-3148.1991.tb00006.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved in‐vitro quality of platelet concentrates stored in a dextrose‐free synthetic medium

Abstract: The licensed balanced salt solution Plasma-Lyte, buffered with a clinical solution of sodium bicarbonate, was evaluated as a suspending fluid for platelet concentrates. Platelets suspended in this medium showed better pH maintenance over 5 days of storage compared to platelets stored in plasma (7.0 vs 6.45, P < 0.001). This was reflected in improvements in in-vitro indicators of platelet viability-hypotonic shock response (79 vs 48%, P < 0.05), aggregation to paired agonists (86 vs 62%, P < 0.05); and platelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…A more direct comparison by the use of a paired study confirmed our previous find ings that platelets suspended in a dextrose-free synthetic medium generated lower amounts of lactate than platelets suspended in plasma [12]. This resulted in higher pH val ues in platelets suspended in the synthetic medium, but in contrast to our previous study in vitro parameters were inferior to those in plasma, particularly in concentrates which were not supplemented with citrate to levels found in CPD platelets.…”
Section: Storage Dayssupporting
confidence: 85%
See 2 more Smart Citations
“…A more direct comparison by the use of a paired study confirmed our previous find ings that platelets suspended in a dextrose-free synthetic medium generated lower amounts of lactate than platelets suspended in plasma [12]. This resulted in higher pH val ues in platelets suspended in the synthetic medium, but in contrast to our previous study in vitro parameters were inferior to those in plasma, particularly in concentrates which were not supplemented with citrate to levels found in CPD platelets.…”
Section: Storage Dayssupporting
confidence: 85%
“…Red cell and platelet concentrates were prepared from blood dona tions as described [12], In this study, component preparation and sampling were complete within 2 h of blood collection -'fresh' unitsor were delayed for an 18-hour period at 22 °C. Red cells were supended in 100 ml of additive solution.…”
Section: Preparation Of Blood Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon (which manifests as a small decrease in lactate concentrations after glucose and glycogen have been exhausted) has been discussed more fully in a previous paper (Niu et al, 1996) and could be significant in the context of possible fuels for synthetic storage media. It is interesting that both a decrease in lactate concentration and/or an increase in pH in low glucose media during storage have been noted previously, but the implications of this set of changes were not initially appreciated (Holme et al, 1987a;Farrugia et al, 1991;Murphy et al, 1991). However, more recently the mechanism involved in these changes has been outlined (Bertolini et al, 1992), and it has been shown that the oxidation of organic acids can have a significant effect on pH changes during platelet storage (Murphy, 1995).…”
Section: Carbohydrate Metabolismmentioning
confidence: 99%
“…Although several groups have reported satisfactory storage of platelets in additive solutions lacking plasma and glucose (Kilkson et al, 1984;Rock et al, 1985; Adams & Rock, 1988;Erikson & Hijgman, 1990;Guppy et al, 1990;Farrugia et al, 1991;hdurphy et al, 1991;Bertolini et al, 1992b) the presence of residual plasma, at a concentration of 10-15%, contributing 3 mmol/l glucose and other fuels, has not allowed a conclusion to be reached as to whether glucose or some other component of plasma is required for maintenance during storage.…”
mentioning
confidence: 99%